2016
DOI: 10.1016/j.jphs.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urate-lowering agents on arrhythmia vulnerability in post-infarcted rat hearts

Abstract: Hyperuricemia has been shown to be associated with ventricular arrhythmias. However, the mechanisms remained unknown. We assessed whether different urate-lowering agents can attenuate arrhythmias through lowering urate itself or inhibiting xanthenes oxidize (XO) activity in infarcted rats. Male Wistar rats after ligating coronary artery were randomized to either allopurinol, or febuxostat, chemically unrelated inhibitors of XO, benzbromarone or vehicle for 4 weeks. Post-infarction was associated with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…NCT00181155 Phase II, NCT00997542 Phase IV) are presented in [146]. Mechanistically, febuxostat improved oxidative stress parameters, adverse protein kinase signaling (phospho-Erk and phospho-mTOR), mitochondrial as well as cardiac function, apoptosis parameters and arrhythmia in animal models of cardiac hypertrophy, myocardial infarction and heart failure [198][199][200][201].…”
Section: Redox Drugs In Clinical Use Against Ischemia/reperfusion Injury and Heart Failurementioning
confidence: 99%
“…NCT00181155 Phase II, NCT00997542 Phase IV) are presented in [146]. Mechanistically, febuxostat improved oxidative stress parameters, adverse protein kinase signaling (phospho-Erk and phospho-mTOR), mitochondrial as well as cardiac function, apoptosis parameters and arrhythmia in animal models of cardiac hypertrophy, myocardial infarction and heart failure [198][199][200][201].…”
Section: Redox Drugs In Clinical Use Against Ischemia/reperfusion Injury and Heart Failurementioning
confidence: 99%
“…Autonomic nervous system activation can induce significant and heterogeneous changes of atrial electrophysiology and induce atrial tachyarrhythmias, including atrial tachycardia and AF (38). Recently, some researchers showed that a continuous 4 weeks inhibition of XO in infarcted rats down-regulated sympathetic innervation (39). This suggests that UA involves in sympathetic nerve activity via sympathetic innervation probably through a superoxide-dependent pathway, which eventually contributes to arrhythmia.…”
Section: The Role Of Oxidative Stress On the Progress Of Elevated Ua-mentioning
confidence: 99%
“…But it is controversial whether hyperuricemia is only a marker of oxidative stress or directly induce VT/VF in STEMI patients. Use of allopurinol significantly decreased the inducibility of ventricular tachycardia and ventricular fibrillation in infarcted rats by down-regulating sympathetic innervation through a superoxide-dependent pathway, but the uricosuric agent benzbromarone had no beneficial effects on oxidative stress, sympathetic hyperinnervation or arrhythmia vulnerability at the similar levels of uric acid [ 27 ], indicating that uric acid functions only as an indicator of xanthine oxidase (XO) activity and is not directly involved in the arrhythmogenic process. However, there are well-established interspecies differences in intrinsic levels of myocardial XO activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%